Awareness and Stock Market Participation - Guiso, Luigi; Jappelli, Tullio (Review of Finance, 2005)
Abstract The paper documents lack of awareness of financial assets in the 1995 and 1998 Bank of Italy Surveys of Household Income and Wealth. It then explores the determinants of awareness, and finds that the probability that survey respondents are aware of stocks, mutual funds and investment accounts is positively correlated with education, household resources, long-term bank relations and proxies for social interaction. Lack of financial awareness has important implications for understanding the stockholding puzzle and for estimating stock market participation costs.